RST1 and RIPR connect the cytosolic RNA exosome to the Ski complex in Arabidopsis - Heike Lange (Nature Portfolio, 2019)
Cytosolic RNA degradation by the RNA exosome requires the Ski complex. Here the authors show that the proteins RST1 and RIPR assist the RNA exosome and the Ski complex in RNA degradation, thereby preventing the production of secondary siRNAs from endogenous mRNAs.